Games and toys: which ones and why? (Journal of Parents and Teachers, 2026)
Psychologists have placed different emphases in their theories about play, but they all agree on its importance for mental, physical, social and emotional development. Play not only helps children to establish their place in the world, release their impulses and gain independence, amongst other things; play is also learning. Throughout the different stages of development, there is also a process of change in the types of play. Initially, these are sensorimotor games, followed by symbolic play and then games with rules. It is also important that toys possess certain educational and physical characteristics so that they can fulfil their purpose at each stage. Here are some guidelines to help you choose them.
Keywords: games; toys; stages of development; learning